Study of the life cycle of Amblyommadubitatum (Acari: Ixodidae) based on field and laboratory data - Debárbora, Valeria Natalia (2014)
The life cycle of Amblyomma dubitatum was described based on the seasonal distribution of all parasitic stages and the development periods of engorged ticks under different conditions of photoperiod and temperature. All stages were found active along the entire year in the study area. Larvae peaked from May to July, nymphs peaked from July to October, and females peaked from November to March. This pattern represents a life cycle with one generation per year with most of the ticks reaching adulthood during the warmest months. The analysis of the effect of the photoperiod on the development of A.dubitatum showed no indication of morphogenetic diapause. Exposure of ticks to field conditions indicates a delay in metamorphosis of immature stages, in the oviposition of females and in the incubation of eggs, which were associated with low winter temperatures. The results indicate that though A. dubitatum has a one year life cycle, more than one cohort can co-exist within the same population in a certain interval of time. Finally, the potential role of small rodents as hosts for larvae and nymphs of A. dubitatum is confirmed.